A atuação no Estado do Paraná da rede de proteção dos direitos dos adolescentes jogadores de futebol na categoria de base: alcance e limitações. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The present research aimed to investigate the procedure of football youth categories of non-training in relation to the protective legislation in the scope of the adolescent football player rights. The investigation started from the hypothesis that there is a gap between the protective legislation about adolescent football player rights and the respect of these rights by their junior clubs of non-training. In order to study this situation, this is an applied, exploratory research with a qualitative approach. The documentary corpus was composed of 09 semi-structured interviews with members of the protection network for the rights of children and adolescentes. These interviewed have competence to inspect the adolescent football players rights from youth categories of both Sport Club Campo Mourão and Prudentópolis Futebol Clube. It was also interviewed an integral member of Prudentópolis Futebol Clube, and the analysis was composed by institutional documents as well. For the analysis of qualitative data, the technique of Content Analysis was adopted. After the analysis, it was found that there is a perception by the protection network members regarding the disrespect to the list of rights of these adolescents. The youth categories of these football clubs permeate the protective legal system, violating their fundamental guarantees constitutionally contemplated (CRFB/1988), as well as its infra-constitutional norms (ECA, Lei Pelé and CLT), even in the administrative norms of sports management entities, such as the CBF and the FPF. However, this veiled and silent structural violence comes to light when complaints of these abuses occur, but above all those with great media repercussion.
Keywords: Direitos dos Adolescentes; Rede de Proteção; Categorias de Base de Futebol; Adolescents’ rights; Protection network; Football youth categories; CNPQ::CIENCIAS SOCIAIS APLICADAS